Downregulation of the protein synthesis machinery is a major regulatory event during early adipogenic differentiation of human adipose-derived stromal cells - Marcon, Bruna H. (2017)
Commitment of adult stem cells involves the activation of specific gene networks regulated from transcription to protein synthesis. Here, we used ribosome profiling to identify mRNAs regulated at the translational level, through both differential association to polysomes and modulation of their translational rates. We observed that translational regulation during the differentiation of human adipose-derived stromal cells (hASCs, also known as adipose-derived mesenchymal stem cells), a subset of which are stem cells, to adipocytes was a major regulatory event. hASCs showed a significant reduction of whole protein synthesis after adipogenic induction and a downregulation of the expression and translational efficiency of ribosomal proteins. Additionally, focal adhesion and cytoskeletal proteins were downregulated at the translational level. This negative regulation of the essential biological functions of hASCs resulted in a reduction in cell size and the potential of hASCs to migrate. We analyzed whether the inactivation of key translation initiation factors was involved in this observed major repression of translation. We showed that there was an increase in the hypo phosphorylated forms of 4E-BP1, a negative regulator of translation, during early adipogenesis. Our results showed that extensive translational regulation occurred during the early stage of the adipogenic differentiation of hASCs.